The Congo's Salonga Park : Interactions between society, biodiversity and water in a humid tropical forest - Inogwabini, Bila-Isia (Brill | Wageningen Academic, 2024)
This book examines interactions between human communities and the global biodiversity that is sheltered by the Salonga National Park. While not being a review of research that has been on-going in the Salonga National Park over several years now